Report of the president to the Board of Regents. - University of the Philippines (Quezon City [s.n.], 1997)
Annual.
A report covering Jan.1-Aug.31, 1934 was issued by the acting president.
Annual reports for the years 1931/32-1933/34 were not printed.
Imprint varies: 1911/12-1930/31, Manila, Bureau of Printing [etc.]-1934-19 Manila, University of the Philippines.
Report year irregular.
Title varies slightly.